Judicial Review of the Legality of Law Enforcement Actions in Pretrial Proceedings: An Analysis of the Makassar District Court Decision No. 36/Pid.Pra/2023/PN Mks - St Fatimah; La Ode Husen; Nur Fadhilah Mappaselleng (Fakultas Hukum, Universitas Muslim Indonesia, 2026)
This study aims to analyze the legality of law enforcement actions in pretrial proceedings, particularly concerning the determination of suspect status, arrest, and detention, as reflected in the Decision of the Makassar District Court No. 36/Pid.Pra/2023/PN Mks. The research employs a normative juridical method with statute, case, and conceptual approaches. The findings indicate that the judge in the pretrial decision emphasized formal legality and procedural compliance in assessing the validity of investigative actions. The determination of suspect status, arrest, and detention were declared lawful due to the existence of at least two valid pieces of evidence and the fulfillment of procedural requirements in accordance with the Criminal Procedure Code. The Applicant’s arguments were rejected primarily due to the ضعف of evidentiary support, particularly the inability to demonstrate concrete procedural violations. In contrast, the Respondent successfully presented systematic and consistent documentary evidence demonstrating adherence to legal procedures. The study further reveals that pretrial proceedings in practice tend to function as a mechanism of administrative control rather than a substantive review of evidentiary quality. This condition raises concerns regarding the effectiveness of pretrial proceedings in protecting human rights. Therefore, strengthening evidentiary standards and expanding the scope of judicial review are necessary to ensure more comprehensive legal protection